2014
DOI: 10.1603/an13136
|View full text |Cite
|
Sign up to set email alerts
|

Intratree Variation in the Seasonal Distribution and Mortality of Spruce Budworm (Lepidoptera: Tortricidae) from the Peak to Collapse of an Outbreak

Abstract: A 5-yr field study was carried out to assess intratree variations in the distribution, abundance, and mortality of immature spruce budworm (Choristoneura fumiferana Clemens) (Lepidoptera: Tortricidae) from the peak to collapse of an outbreak. In most years, the highest density of overwintering second-instar (L2) larvae (per square meter of foliage) was located in the lower crown, whereas all subsequent stages (third-to sixth-instar larvae, pupae, and eggs) were at relatively higher densities in the upper crown… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 36 publications
0
19
0
Order By: Relevance
“…It is known that the spruce budworm parasitoid community changes through time and that different species attack different developmental stages of the host (Eveleigh and Johns 2014). Because of these temporal changes, species involved in consecutive parasitoid communities may be affected by different environmental features.…”
Section: Study Region and Data Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is known that the spruce budworm parasitoid community changes through time and that different species attack different developmental stages of the host (Eveleigh and Johns 2014). Because of these temporal changes, species involved in consecutive parasitoid communities may be affected by different environmental features.…”
Section: Study Region and Data Collectionmentioning
confidence: 99%
“…). The parasitoid community also varies in composition within a single season due to differences in parasitoid species phenology (Eveleigh and Johns , Seehausen et al. ).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, logging could be an important factor to understand red spruce ecosystem in GSMNP between 1940and 1979(Harmon et al, 1984. Also, red spruce is consumed by several insects (Eveleigh and Johns, 2014;MacKinnon and MacLean, 2004). However, no research has found a specialized relationship among the insects and logging and red spruce growth declines in the GSMNP.…”
Section: Reconciling These Conflicting Studiesmentioning
confidence: 99%
“…This could be due to factors such as dispersal, competition between co-existing species, human disturbance by logging, and physical environmental conditions not considered in ARIM.SIMs due to the lack of literature information. For example, red spruce is consumed by several insects, such as spruce budworm (Choristoneura fumiferana) (Eveleigh and Johns, 2014;MacKinnon and MacLean, 2004), hemlock looper (Lambdina fiscellaria) (Alfaro et al, 1999). However, no research has found a specialized relationship between the insects and red spruce in the GSMNP.…”
Section: Resultsmentioning
confidence: 99%